(untitled) (Research, Society and Development, 2021)
The present study aimed to evaluate the accuracy of cranial measurements for estimation of sex in the Brazilian population and develop discriminant formulas with a reference table to be used as a reference on Brazilian Forensic Anthropology studies. The total sample was comprised of 100 skulls from an osteological collection and 200 computed tomography. The measure’s protocol comprised 51 cranial measurements and it was based on 29 cranial landmarks. The results of the univariate comparison of cranial measurements showed a higher mean for male skulls, except for the following variables: zygoorbital breadth (diff=-2.21), interorbital breadth (diff=-0.72), nasal breadth (diff=-0.19) and palatal breadth (diff=-0.01). The paired test t analysis showed that the variables with the highest sexual dimorphism were maximum cranial length (p<0.001), Basion-Bregma height (p<0.001), cranial base length (p<0.001), nasal height (p<0.001), bizigomatic breadth (p<0.001), left Porion-Mastoidale length (p<0.001), right Asterion-Mastoidale length (p<0.001), right (p<0.001) and left (p<0.001) mastoid length. The multivariate discriminant analysis of the cranial measurements of the Brazilian sample showed a percentage of accuracy between 82-90%. The analysis of the metric variables showed that there is sexual dimorphism between skulls in the sample. The regression formulas and the reference table presented satisfactory results for sex estimation in a Brazilian population. The validation process of the discriminant functions and the reference table showed a percentage of accuracy between-74.2-85.7% The analysis of the metric variables showed that there is sexual dimorphism between skulls of the analyzed sample.